Vasoactive intestinal polypeptide regulation of rabbit renal adenylate cyclase activity in vitro. - Griffiths, N M (1987)
1. The effect of vasoactive intestinal polypeptide (VIP) upon adenylate cyclase activity was determined in purified cortical basolateral membranes and in glomeruli and tubular elements obtained from rabbit kidney. 2. In purified basolateral membranes prepared from cortex, 1 microM-VIP consistently stimulated adenylate cyclase activity above basal levels (1.55 +/- 0.09-fold (mean +/- S.E. of mean), n = 10 animals). Half-maximal stimulation was observed at 17 +/- 11 nM-VIP (S.D., n = 9). 3. Related peptides, e.g. secretin, glucagon, gastric inhibitory peptide, human pancreatic growth hormone releasing factor, and peptide having N-terminal histidine and C-terminal isoleucine amide (PHI), were without effect or gave lower stimulations of adenylate cyclase activity when tested at 1 microM. 4. Significant VIP degradation was observed under the assay conditions used but this did not substantially alter the response or selectivity to VIP. 5. In separate preparations of isolated glomeruli and proximal tubules addition of 1 microM-VIP resulted in a 3.3 +/- 1.1-fold (S.D., n = 3) and 2.2 +/- 1.0-fold (S.D., n = 3) stimulation (respectively) of adenylate cyclase activity. 6. In isolated medullary tubule suspensions, isolated by collagenase-hyaluronidase digestion of outer (red) medulla, and in thick ascending-limb-enriched preparations prepared by Percoll density gradient fractionation, 1 microM-VIP significantly increased adenylate cyclase activity by 2.4 +/- 0.6-fold (S.D., n = 3) and 2.1 +/- 0.7-fold (S.D., n = 3) respectively. 7. A possible role for VIP in the regulation of renal function in the rabbit is discussed in relation to the occurrence of VIP stimulation of adenylate cyclase activity in several renal cellular elements.